Siamese twins: case report - Gutierrez Delgado, Ingrid (2015)
A case of thoracopagus conjoined twins with ultrasound antenatal diagnosis is presented. Ultrasound study in a 14 yearold young mother in her first pregnancy revealed twin pregnancy variety thoracopagus-xiphopagus 23,4 weeks by biometry. She was admitted at Hospital Nacional Madre-Nino San Bartolome where classical corporal cesarean section plus B. Lynch technique were performed and female thoracopagus preterm live newborns were obtained. Pathology confirmed diagnosis. Summary of the clinical history and necropsy protocol are presented.